Análise do uso das TICs em escolas públicas e privadas a partir da teoria da atividade - Willian Washington Wives; Luis Claudio Kubota; Tel Amiel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– School technology integration rarely begins with school or educator choice. It is part of a wider context where external and internal factors have direct influence on the goals and tools that are adopted over time. The objective of this discussion paper is to investigate the systemic conditions that contribute or inhibit the development of different activities by teachers making use of new media. We compiled a list of well-known conditions for technology integration success and mapped these in the historical and culturally bound perspective of cultural-historical activity theory (CHAT). We conducted a multiple case-study analysis of four schools, public and private. Among the main results, we can highlight the following: the importance of the leadership for an integrated use of ICTs in the schools, proactivity as a means to overcome material limitations (for the public schools), material conditions do not necessarily translate in more advanced practices in ICT use, different levels of ICT use do not have any structural relation with the change in traditional teacher and student roles. Case studies such as this have to be analyzed with caution when trying to generate inferences to school systems as a whole. On the other hand, study proposes a methodology that can help elicit tensions in technology integration, pointing to avenues for school development.
Keywords: I2; 330; school; activity theory; information and communication technologies; new media